Perlindungan Hukum Bagi Kreditur Terhadap Perampasan Objek Jaminan Fidusia Oleh Negara - Moh. Saleh; Dwi Fajra Fakhrizal (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
Creditors and debtors have entered into numerous fiduciary guarantee agreements; creditors play a critical role in economic activity in general and in the guarantee in particular. Numerous cases have harmed creditors over time, but legal protection against creditors is still considered weak due to a lack of regulations strengthening creditors' ability to assert their rights. Then, the need for legal certainty in fiduciary agreements is addressed through normative juridical means, as the case of fiduciary agreements has encountered issues relating to the object of fiduciary assurances taken by the state in order to provide creditors with a strong basis for demanding legal protection of their rights. The purpose of this study is to ascertain the legal consequences of seizing fiduciary guarantee objects and to provide legal protection against creditors asserting their rights, as the Fiduciary Guarantee Law continues to have a weak regulatory foundation due to its imbalanced approach to the execution of fiduciary guarantees between creditors and debtors. As a result, socialization of the implementation of fiduciary guarantees and strict legal protection for creditors is expected.Keywords: guarantee, fiduciary, legal protection. AbstrakPerjanjian jaminan fidusia sudah banyak yang dilakukan oleh para kreditur dan debitur, kreditur mempunyai peran yang sangat penting bagi kegiatan ekonomi pada umumnya serta adanya penjaminan khususnya. Seiring berjalannya waktu banyak kasus yang merugikan pihak kreditur akan tetapi perlindungan hukum terhadap pihak kreditur hingga saat ini masih dianggap lemah sebab masih kurangnya peraturan yang menguatkan kreditur apabila ingin menuntut haknya. Maka perlu adanya kepastian hukum didalam perjanjian fidusia melalui yuridis normatif, sebab dalam perkembangannya kasus perjanjian fidusia memiliki permasalahan terkait dengan objek jaminan fidusia yang di rampas oleh negara, maka agar kreditur memiliki dasar yang kuat untuk menuntut haknya perlu perlindungan hukum. Penelitian ini bertujuan untuk mengetahui akibat hukum dari adanya perampasan objek jaminan fidusia serta perlindungan hukum terhadap kreditur untuk menuntut haknya, sebab dalam Undang-undang Jaminan Fidusia masih memiliki dasar pengaturan yang lemah sebab tidak diimbangi ketegasan dalam pelaksanaan eksekusi jaminan fidusia antara kreditur dan debitur. Maka diharapkan perlu adanya sosialisasi terkait dengan pelaksanaan jaminan fidusia dan perlindungan hukum yang tegas bagi kreditur.Kata Kunci : Jaminan, fidusia, perlindungan hukum.